2006
DOI: 10.1269/jrr.47.183
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Enhances Radiation-Triggered Apoptosis in Non-Hodgkin's Lymphoma Cells Via Caspase-dependent and - Independent Mechanisms

Abstract: Rituximab (RTX), a chimeric human anti-CD20 monoclonal antibody, is currently employed in the treatment of malignant non-Hodgkin's lymphoma (NHL) either alone or in combination with other cytotoxic approaches. The present study examines the effects of ionizing radiation in combination with RTX on proliferation and apoptosis development in B-lymphoma RL and Raji cells. RTX was used at a concentration of 10 microg/mL 24 hours prior to irradiation at a single dose of 9 Gy. CD20 expression, cell viability, apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 51 publications
1
29
0
2
Order By: Relevance
“…Nevertheless, several patients who received a predose of 685 mg of tositumomab before the 131 I-tositumomab imaging dose experienced tumor shrinkage even before they were administered the 131 Itositumomab therapy dose, and these patients were more likely to have a better response after the therapy dose (29,30). As the mechanism of action of anti-CD20 antibodies was examined further, the activation of apoptotic signaling of the antibody drew attention to its ability to sensitize cells to radiation (31,32). Thus, it is understandable that these predosing regimens were instituted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several patients who received a predose of 685 mg of tositumomab before the 131 I-tositumomab imaging dose experienced tumor shrinkage even before they were administered the 131 Itositumomab therapy dose, and these patients were more likely to have a better response after the therapy dose (29,30). As the mechanism of action of anti-CD20 antibodies was examined further, the activation of apoptotic signaling of the antibody drew attention to its ability to sensitize cells to radiation (31,32). Thus, it is understandable that these predosing regimens were instituted.…”
Section: Discussionmentioning
confidence: 99%
“…31 Subsequent findings have indicated that an anti-CD20 IgG predose radiosensitizes the cells, thereby providing some added benefit to the combination treatment. [32][33][34][35] Parenthetically, Kapadia et al found that lower doses of rituximab radiosensitize cells, while higher doses actually appeared to be protective. 34 Both preclinical and clinical data clearly supported the value of administering a predose of the unlabeled anti-CD20 IgG to improve tumor targeting and extend the residence time of the radioimmunoconjugates in the blood; certainly, by using this approach, the radiolabeled agents were able to improve the objective response rate compared with their corresponding unlabeled antibody.…”
Section: Current Radioimmunoconjugate Therapy Of Nhl: Development Andmentioning
confidence: 99%
“…Furthermore, rituximab has been shown to increase the sensitivity of lymphoma cells for external beam radiation. 45 The question can, however, be raised whether regression of lymphoma at distant sites in our study could be because of a direct systemic effect of rituximab. We believe that this is unlikely because the total dose of 30 mg of rituximab administered in lymph nodes is ;100-fold less than normally used for single-agent rituximab therapy.…”
Section: Discussionmentioning
confidence: 72%